Analysis of outcomes of emergency general and gastrointestinal surgery during the COVID-19 pandemic. Issue 12 (18th September 2021) - Osorio, J; Madrazo, Z; Videla, S; Sainz, B; Rodríguez-González, A; Campos, A; Santamaría, M; Pelegrina, A; González-Serrano, C; Aldeano, A; Sarriugarte, A; Gómez-Díaz, C J; et al.
Abstract: Background: Few surgical studies have provided adjusted comparative postoperative outcome data among contemporary patients with and without COVID-19 infection and patients treated before the pandemic. The aim of this study was to determine the impact of performing emergency surgery in patients with concomitant COVID-19 infection. Methods: Patients who underwent emergency general and gastrointestinal surgery from March to June 2020, and from March to June 2019 in 25 Spanish hospitals were included in a retrospective study (COVID-CIR). The main outcome was 30-day mortality. Secondary outcomes included postoperative complications and failure to rescue (mortality among patients who developed complications). Propensity score-matched comparisons were performed between patients who were positive and those who were negative for COVID-19; and between COVID-19-negative cohorts before and during the pandemic. Results: Some 5307 patients were included in the study (183 COVID-19-positive and 2132 COVID-19-negative during pandemic; 2992 treated before pandemic). During the pandemic, patients with COVID-19 infection had greater 30-day mortality than those without (12.6 versus 4.6 per cent), but this difference was not statistically significant after propensity score matching (odds ratio (OR) 1.58, 95 per cent c.i. 0.88 to 2.74). Those positive for COVID-19 had more complications (41.5 versus 23.9 per cent; OR 1.61, 1.11 to 2.33) and a higher likelihood of failure to rescue (30.3 versus 19.3 per cent; OR 1.10, 0.57 to 2.12). Patients who were negative for COVID-19 during the pandemic had similar rates of 30-day mortality (4.6 versus 3.2 per cent; OR 1.35, 0.98 to 1.86) and complications (23.9 versus 25.2 per cent; OR 0.89, 0.77 to 1.02), but a greater likelihood of failure to rescue (19.3 versus 12.9 per cent; OR 1.56, 95 per cent 1.10 to 2.19) than prepandemic controls. Conclusion: Patients with COVID-19 infection undergoing emergency general and gastrointestinal surgery had worse postoperative outcomes than contemporary patients without COVID-19. COVID-19-negative patients operated on during the COVID-19 pandemic had a likelihood of greater failure-to-rescue than prepandemic controls. Abstract : This multicentre cohort study included 2315 patients who underwent general and digestive emergency surgery from March to June 2020, and 2992 prepandemic controls. Propensity score-matched analysis showed that COVID-19 infection was significantly associated with complications (40.6 versus 29.9 per cent) and death (12.0 versus 8.1 per cent), and that COVID-19-negative patients with postoperative complications during the pandemic had a significantly higher risk of death than prepandemic controls (18.8 versus 13.0 per cent). Therefore, both COVID-19 infection and inefficient rescue of complications associated with hospitals being overwhelming during the pandemic had a negative impact on postoperative outcomes after emergency surgery.